Where is the development in SA’s developmental state? - Matisonn, John (New Agenda: SA Journal of Social and Economic Policy, 2024)
The ruling party defines South Africa as a ‘developmental state’, but with its rising job losses, growth that is lower than most of its African neighbours and rising inequality can that really apply? What’s missing, asks John Matisonn.